Cytogenetic evidence for diversity of two nuclei within a single diplomonad cell of Giardia - Tůmová, Pavla; Hofštetrová, Klára; Nohýnková, Eva; Hovorka, Ondřej; Král, Jiří (Chromosoma, 2007)
Giardia intestinalis is an ancient protist that causes the most commonly reported human diarrheal disease of parasitic origin worldwide. An intriguing feature of the Giardia cell is the presence of two morphologically similar nuclei, generally considered equivalent, in spite of the fact that their karyotypes are unknown. We found that within a single cell, the two nuclei differ both in the number and the size of chromosomes and that representatives of two major genetic groups of G. intestinalis possess different karyotypes. Odd chromosome numbers indicate aneuploidy of Giardia nuclei, and their stable occurrence is suggestive of a long-term asexuality. A semi-open type of Giardia mitosis excludes a chromosome interfusion between the nuclei. Differences in karyotype and DNA content, and cell cycle-dependent asynchrony are indicative of diversity of the two Giardia nuclei.
Keywords: Giardia; Cell Nucleus; aparát dělícího vřeténka; Cell Cycle; cytogenetické vyšetření; protozoální DNA; financování organizované; mitóza; Financing, Organized; buněčné jádro; DNA, Protozoan; zvířata; Spindle Apparatus; Mitosis; karyotypizace; Animals; Cytogenetic Analysis; buněčný cyklus; Karyotyping